Designing artificial magnetic conductor at 2.45 Ghz for metallic detection in RFID tag application - Abu, Maisarah; Hussin, Eryana Eiyda (2014)
In this paper, three types of AMC with different shape and design is discussed. The single unit cell Halfring AMC designed in this paper had increased the bandwidth up to 9.46%. Parametric studies were conducted for those three AMCs to investigate the effect of varying the parameters of each design. The values of gain, directivity and return loss for all AMCs is discussed and compared. From the simulated result, when the dipole is attached on Perfect Electric Conductor, PEC the performance of antenna will drop severely. The new Halfring AMC designed in this paper had overcome the problem of metallic object detection in RFID tag application. The simulated result shows that the Halfring AMC at half-lambda size had increased the performance of dipole antenna with return loss = -22.60 dB, gain = 7.58 dB and directivity of 8.15 dBi.